2023
DOI: 10.1002/adma.202300659
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ultra‐Wideband Electromagnetic‐Wave‐Absorbing Metastructure Inspired by Bionic Gyroid Structures

Abstract: Traditional honeycomb‐like structural electromagnetic (EM)‐wave‐absorbing materials have been widely used in various equipment as multifunctional materials. However, current EM‐wave‐absorbing materials are limited by narrow absorption bandwidths and incidence angles because of their anisotropic structural morphology. The work presented here proposes a novel EM‐wave‐absorbing metastructure with an isotropic morphology inspired by the gyroid microstructures seen in Parides sesostris butterfly wings. A matching r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 54 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Considering this trend, the KF-EMA would be beneficial in the repetitive loading environments or irregular loading disturbances. Lastly, the comparison table with other studies presents the outstanding characteristics of KF-EMA representing the 3D-printed RAS employing bending-dominated structures, in terms of facile fabrication, scalable material selection, and multifunctionality [15,[40][41][42][43][44][45][46] (Table S1, Supporting Information).…”
Section: Experimental Demonstration Of Em-absorbing Performance and M...mentioning
confidence: 99%
“…Considering this trend, the KF-EMA would be beneficial in the repetitive loading environments or irregular loading disturbances. Lastly, the comparison table with other studies presents the outstanding characteristics of KF-EMA representing the 3D-printed RAS employing bending-dominated structures, in terms of facile fabrication, scalable material selection, and multifunctionality [15,[40][41][42][43][44][45][46] (Table S1, Supporting Information).…”
Section: Experimental Demonstration Of Em-absorbing Performance and M...mentioning
confidence: 99%
“…The remaining unconsumed electromagnetic wave will pass through the material and will be transmitted into the air. 1–5 The EMW attenuation mechanism is depicted in Fig. 1a.…”
Section: Introductionmentioning
confidence: 99%
“…Recently research has begun to explore the potential of 3D printed structures to achieve multifunctionality. This is achieved by employing lightweight, load-bearing mechanical metamaterials as EMA, such as gyroid, 24 octet-truss, 25 and kelvin-foam 26 structures. Similar to honeycomb design, these structured porous mechanical metamaterials enable enhanced attenuation through structural absorption.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, An et al demonstrated a gyroid-structured 3D printed metasurface capable of achieving a broadband reflection loss (−10 dB) across a 2–40 GHz range. 24 Their study examined the impact of various geometrical parameters, such as volume fraction, strut/sheet configurations in gyroid, and unit cell length, on attenuation performance. The octet-truss, recognized for its low-density and robust mechanical, has also shown significant promise as an effective multifunctional EMA 25 offering improved isotropic mechanical strength and EM wave absorption due to its unique unit cell geometry.…”
Section: Introductionmentioning
confidence: 99%